Hepatobiliary Scintigraphy to Evaluate Biliary Complications of Pediatric Liver Transplantation: An Account of an Experience - Gutierrez-Villamil, Claudia; Velez-Gutierrez, Camila; Arevalo-Leal, Sinay; Rivera-Baquero, Jairo; Marín-Oyaga, Víctor (European Journal of Pediatric Surgery, 2020)
Introduction Hepatobiliary scintigraphy (HS) is a noninvasive imaging technique whose use in the follow-up of liver transplantation has not been duly documented. The main objective of this study is to describe the experience of using this technique to detect biliary complications in pediatric patients following liver transplantation.Materials and Methods A retrospective, observational, and descriptive study involving 86 pediatric patients who had undergone liver transplantation between 2013 and 2018. Of the 86, 31 had undergone at least one HS during their postoperative period.Results A total of 45 studies were performed on 31 patients (36% of the patients undergoing transplantation during that time period). Patient ages ranged from 5 to 204 months (mean = 50 months). A total of 22 transplants (71%) were from living donors and 9 (29%) were from cadaveric donors. Of the 45 studies, 22 were positive for biliary complications, and all of them had an impact on clinical decision-making. The remaining 23 studies were negative. Of these 23, 19 continued under medical treatment and the other four underwent an additional intervention with positive surgical outcomes in all cases. All scintigraphy studies revealed hepatocellular dysfunction and cholestasis.Conclusion The HS is a useful, noninvasive, and diagnostic procedure for the early diagnosis of biliary complications that may impact the evolution of disease in liver transplant patients. It allows the treating physician to make a more informed decision regarding expectant management, surgical management, or a less invasive course of action for transplantation complications.
Keywords: hepatobiliary scintigraphy; pediatric liver transplantation; biliary complications